Age hardening in superhard ZrB2-rich Zr1-xTaxBy thin films. (15th January 2021) - Bakhit, Babak; Palisaitis, Justinas; Wu, Zhengtao; Sortica, Mauricio A.; Primetzhofer, Daniel; Persson, Per O.Å.; Rosen, Johanna; Hultman, Lars; Petrov, Ivan; Greene, J.E.; Greczynski, Grzegorz
Abstract: We recently showed that sputter-deposited Zr1-x Tax By thin films have hexagonal AlB2 -type columnar nanostructure in which column boundaries are B-rich for x < 0.2, while Ta-rich for x ≥ 0.2. As-deposited layers with x ≥ 0.2 exhibit higher hardness and, simultaneously, enhanced toughness. Here, we study the mechanical properties of ZrB2.4, Zr0.8 Ta0.2 B1.8, and Zr0.7 Ta0.3 B1.5 films annealed in Ar atmosphere as a function of annealing temperature T a up to 1200 °C. In-situ and ex-situ nanoindentation analyses reveal that all films undergo age hardening up to T a  = 800 °C, with the highest hardness achieved for Zr0.8 Ta0.2 B1.8 (45.5±1.0 GPa). The age hardening, which occurs without any phase separation or decomposition, can be explained by point-defect recovery that enhances chemical bond density. Although hardness decreases at T a > 800 °C due mainly to recrystallization, column coarsening, and planar defect annihilation, all layers show hardness values above 34 GPa over the entire T a range. Graphical abstract: Image, graphical abstract